Ragam Branding Desa dalam Mengembangkan Potensi Wisata Berbasis Budaya Masyarakat di Kabupaten Buleleng - Widiastini, Ni Made Ary; Rahmawati, Putu Indah; Isti Koma, Fajar Yualida (Jurnal Master Pariwisata (JUMPA); Volume 07, Nomor 01, Juli 2020, 2020)
This paper aims to describe the image and branding of the cultural potential of a tourist destination in Buleleng Regency, so that each destination can be understood to have a different and unique identity. Buleleng Regency has natural and cultural potential that can be managed and utilized as tourist attractions. The potential can be packaged so that it becomes something that shows the identity of a destination. The large number of same turist destinations requires the accuracy in its management, so that the target market can be achieved. Brand and image become very important as a distinguishing destination between one another. In Buleleng Regency, several places have been developed by create the brand and image as tourist destinations, such as the Old Village of Buleleng Regency which consists of seven villages, Janger Kolok Bengkala Village, Bukakak Tradition, Sudaji Village, Beji Temple, Sangsit Village, Gedong Kerta and Puri in Paket Agung Village, dan Vihara in Banjar Village. In its implementation, it is recommended that brand and image formation must also be accompanied by the provision of facilities and services in accordance with the image being built. Keywords: Brand, Image, Tourism, Buleleng